Bilateral suprascapular nerve entrapment by glenoid labral cysts associated with rotator cuff damage and posterior instability in an amateur weightlifter - Limbucci, N.; Rossi, F.; Salvati, F.; Pistoia, L. M.; Barile, A.; Masciocchi, C. (The Journal of Sports Medicine and Physical Fitness, 2010)
Suprascapular nerve entrapment is a common condition in athletes. The entrapment is most frequently due to a "glenoid labral cyst" produced by joint fluid extrusion in consequence of labral degenerative changes. The bilaterality of the entrapment and the association with rotator cuff pathology are a rare evidence. We present the case of a 38-year-old amateur weightlifter with an history of left shoulder chronic posterior pain and progressive external rotation weakness, and with an acute right shoulder pain and weakness. Magnetic resonance imaging showed a bilateral glenoid labral cyst in association with partial tear of the supraspinatus tendon, atrophy of the infraspinatus muscle and type 2 SLAP lesion at the left shoulder and subacromial impingement syndrome (due to acromio-clavicular osteophyte), mild atrophy of the infraspinatus muscle and type 1-2 SLAP lesion at the right side.